TOWARDS DEMAND DRIVEN PUBLISHING: APPROCHES TO THE PRIORITISATION OF DIGITISATION OF NATURAL HISTORY COLLECTIONS DATA - Chavan, Vishwas; BERENTS, PENNY; HAMER, MICHELLE (Biodiversity Informatics, 2010)
Natural history collections represent a vast repository of biodiversity data of international significance. There is an imperative to capture the data through digitisation projects in order to expose the data to new and established users of biodiversity data. On the basis of review of current state of digitization of natural history collections, a demand driven approach is advocated through the use of metadata to promote and increase access to natural history collection data.